An AI-driven TiO2-NiFeC-PEM microbial electrolyzer for in situ hydrogen generation from POME using a ZnO/PVA-EDLOSC nanocomposite photovoltaic panel - Rahman, Md Ataur; Qatu, Mohamad; Labib, Hassan; Afroz, Rafia; Ghatus, Mehdi; Ihsan, Sany Izan (MDPI, 2025)
Electrolysis and biological processes, such as fermentation and microbial electrolysis cells, offer efficient hydrogen production alongside wastewater treatment. This study presents a novel microbial electrolyzer (ME) comprising a titanium dioxide (TiO2) anode, a nickel–iron–carbon (NiFeC) cathode, and a cellulose nanocrystal proton exchange membrane (CNC-PEM) designed to generate hydrogen from palm oil mill effluent (POME). The system is powered by a 12 V electric double-layer organic supercapacitor (EDLOSC) integrated with a ZnO/PVA-based solar thin film. Power delivery to the TiO2-NiFeC-PEM electrolyzer is optimized using an Adaptive Neuro-Fuzzy Inference System (ANFIS). Laboratory-scale pilot tests demonstrated effective degradation of POME’s organic content, achieving a hydrogen yield of approximately 60%. Additionally, the nano-structured ZnO/CuO–ZnO/PVA solar film facilitated stable power supply, enhancing in situ hydrogen production. These results highlight the potential of the EDLOSC-encased ZnO/PVA-powered electrolyzer as a sustainable solution for hydrogen generation and industrial wastewater treatment